SOCIAL WORK IN MODERN SCIENTIFIC DISCOURSE: THE MILITARY ASPECT - Aleschenko, Viktor; Pozdyshev, Serhiy (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Today, the military aspect of social work is gaining more and more relevance, requiring a significant strengthening of the system of social security and social assistance to the population, proper social protection of military personnel and other persons participating in the protection of state sovereignty. The purpose of the article is to study the military aspect of social work in the armed forces of ukraine, to develop approaches to its systematization and to create an effective model. M e t h o d s . The following methods were used in the research: analysis, generalization, comparison, systematization of scientific sources on the problem of social work research in the Armed Forces of Ukraine. R e s u l t s . The article reveals the military aspect of social work in the structure of socio-humanitarian sciences, and also highlights its features as an applied activity in the Armed Forces of Ukraine. The concept of the importance of the organization of social work, the specific goal of which is the maximum use of legal, organizational, and educational means by its subjects during the performance of assigned duties and granted powers regarding social work in the Armed Forces of Ukraine, was supplemented and expanded. Social work is considered as a system in its organic combination with the general system of social work in the state, which makes it possible to apply appropriate methods of providing assistance and social support to people connected with military activities who need social protection. C o n c l u s i o n s . Without reservations, it can be stated that the effectiveness of combat activities, the fighting spirit of personnel on the battlefield, along with other factors, largely depends on the skillful organization of social work as an important component of building a strong army.